PERENCANAAN SISTEM PENDINGIN PALKA IKAN MENGGUNAKAN TENAGA SURYA - Rizali R (DINAMIS, 2015)
Planning the cooling system box / hatch fishing boats using solar power is intended to inhibitthe growth of bacteria on the fish so as to maintain the freshness and quality and benefit ofsolar energy as a power conditioning sytem hatch fish. At this time fishing boats used by thefishermen on the island of Bengkalis storage of fish using only a block of ice. But a block ofice that has been used for a fixed time limit and gradually shaped ice will melt and no longereffective. Therefore made planning a fishing boat hatch cooling systems using solar power.The test results porformance temperature box / hatch the fish reaches a temperature of -7.3degrees Celsius. Performance bateray capable of supplying the cooling box for 12 ja mwithout voltage supplied through PV modules to bateray the test results show that thecondition bateray still keep the flow by 50%. So that the fish catch fresh condition remains inmaking the price of high-value fish and furnish an alternative method to saving on fuelenergy.